SeeCarbon: a review of digital approaches for revealing and reducing infrastructure, building and City's carbon footprint. Issue 19 (2022) - Yan, Jiayi; Lu, Qiuchen; Chen, Long; Broyd, Tim; Pitt, Michael
Abstract: Dealing with climate change and its consequences on the environment have been one of the biggest challenges nowadays, where reducing the carbon footprint has been the focus of most sustainable strategies. The infrastructure is the dominant sector responsible for the total carbon footprint, accounting for approximately 70% of global carbon emissions. This study aims to illustrate the state-of-the-art of digital development and transformation of revealing and reducing carbon footprint in the Architecture, Engineering, Construction and Facility Management (AEC/FM) sectors. The digital tools for revealing and reducing infrastructure's carbon footprint would be summarized and also compared with other sectors, namely the tools for building and city. Current challenges and future development are also included.